2018
DOI: 10.1186/s12967-018-1411-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating microRNAs as markers in detecting and predicting congenital heart defects in children

Abstract: BackgroundCirculating microRNAs (miRNAs) are emerging as novel biomarkers for detecting cardiovascular diseases. In this study, we aimed to investigate the usefulness of miRNAs as biomarkers in diagnosing and predicting children with congenital heart defects (CHD), particularly in the context of multiple subtypes of CHD.MethodsWe recruited 26 families, each having a child with CHD and parents who do not have any cardiovascular disorder. 27 families unaffected by cardiovascular disease were also included as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…MiRNAs are involved in multiple biological processes including cell proliferation, differentiation, and metabolism [13, 19, 29] by modulating specific genes. It has been shown that miRNAs are abnormally expressed in many types of diseases, including heart disease, inflammatory diseases, and especially cancers [20, 21, 30].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are involved in multiple biological processes including cell proliferation, differentiation, and metabolism [13, 19, 29] by modulating specific genes. It has been shown that miRNAs are abnormally expressed in many types of diseases, including heart disease, inflammatory diseases, and especially cancers [20, 21, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that some miRNAs are correlated with fetal heart diseases. This was determined using peripheral blood samples of pregnant women and these miRNAs were reported to originate in the placenta [24][25][26][27] . In light of this information we believe that specific miRNAs found in the cord blood of fetuses can be used as biomarkers for the antenatal early diagnosis of fetal kidney anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of research on miRNA expression profiles in ASD. Song et al [39] reported that hsa-let-7a, hsa-let-7b and hsa-miR-486 were significantly upregulated in the plasma of children with ASD. A miRNA SNP study indicated that the miR-196a2 (rs11614913 T > C) homozygous CC variant and the C allele are negatively associated with ASD [40].…”
Section: Dynamic Microrna Expression Profile During Heart Developmentmentioning
confidence: 99%